Pengaruh Air Jahe Hangat Dengan Penurunan Mual Muntah Pada Ibu Hamil Trimester I Di PMB Ani Lampung Tengah Tahun 2023 - Nandini Permata Sari; Yuyun Triyani (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Background: Pregnancy is the union of spermatozoa and ovum which is followed by the implantation of the products of conception into the endometrium. Thel gestation periodl starts froml conception tol the birthl of thel fetus. Normall pregnancy durationl is 280l days (40l weeks orl 9 monthsl 7 ldays) counting froml the firstl day ofl the lastl menstruation. Based on the phenomena found in the work area of ​​BPM Ani, Seputih Jaya, Central Lampung in April-May 2023, it was found that 20 pregnant women in their first trimester experienced nausea and vomiting. Aim: Thisl study aimsl to determinel the effectl of giving warm gingerl water onl reducing nauseal and vomitingl in first trimesterl pregnant lwomen. Method: This study used the Pre-Experimental method using the One Group Pre Test Post Test Design research design. Result: This study shows the results of the test with the Wilcoxon test with a result of 0.001 with a significant result of <0.05, Conclusion: so it can be concluded that there is effectiveness of warm ginger water in reducing nausea and vomiting in first trimester pregnant women at BPM Ani, Seputih Jaya in 2023.